Strukturasi Adaptif Penggunaan Teknologi Informasi pada Instansi Pemerintahan - Rosalia, Fanny (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
The implementation of periodic monitoring and evaluation is one of the keys to the successful implementation of bureaucratic reform in an organization. Various ways are carried out so that the implementation of evaluation monitoring is carried out periodically by each organization. Various components become objects that must be monitored and evaluated continuously. This is not an easy thing to do with its various complexities. One of the government agencies has implemented Information Technology as one of the efforts to implement scheduled, up to date and optimally evaluated bureaucratic reforms. With an adaptive structuring theory approach, this study aims to see how the adaptive structuring process in the use of e-monitoring applications qualitatively by interviewing a number of respondents who are Civil Servants in each Working Group in eight areas of bureaucratic reform changes. The results showed that the use of e-monitoring application is the process of structuring information technology on rules and resources produced and reproduced by users in the organization. Then there is an interplay between the information technology structure ofe-monitoring with the structure of features, other structures, and internal organizational systems. Adjustments made in interacting also give rise to a new structure that is continuously carried out by users so that it is legitimized in the use of e-monitoring as a process of monitoring and evaluating the implementation of bureaucratic reforms.